The Effect of Transparency And Accountability on The Quality of Public Financial Reports - Sonang Sipahutar; Nur Fadilla; Rischa Nadapdap; Sayyida Nabila; Galih Supraja (Penerbit Jurnal Indonesia, 2025)
This study aims to analyze the influence of transparency and accountability on the quality of public financial reports. Transparency and accountability are considered key elements in enhancing the trust and credibility of public institutions, especially in financial management. The research employed a quantitative approach, collecting data through surveys and analyzing it using multiple linear regression. The study population consisted of public institutions within a specific region, with samples selected purposively. The findings reveal that transparency and accountability significantly influence the quality of public financial reports. These results imply that strengthening transparency and accountability practices can improve financial report quality, thereby promoting better financial governance. The study suggests that public institutions should continue enhancing transparency and accountability by implementing policies supporting clear, timely, and responsible information disclosure.